Quantifying the Relationship Between Human Activities Intensity and Thawing Hazards of the Frozen Ground on the Qinghai–Tibet Plateau - Ni, Jie; Wu, Tonghua; Zhu, Xiaofan; Chen, Jie; Wu, Xiaodong; Hu, Guojie; Zou, Defu; Li, Ren; Du, Yizhen (Frontiers in Earth Science, 2022)
Climate warming could accelerate frozen ground degradation on the Qinghai-Tibet Plateau (QTP). Quantitative analysis of the impacts of thaw-induced hazards of the frozen ground on human activities in cold regions has become one of the most important issues in current research. To identify adverse impacts of these thawing hazards on human activities, this study explores a spatially explicit, temporally consistent and quantitative method to map human activity intensity (HAI). Four categories of variables are selected to represent some of the most important human activities on the QTP, including land use, road distribution, population density, and grazing density. By improving the human footprint index method, HAI maps of the QTP in 1995, 2005 and 2015 are created, and then quantitative analysis the HAI under different thawing hazard levels in the frozen ground of QTP. The results show that, for the above three periods, the mean HAI values on the QTP are 0.10, 0.11, and 0.12, respectively. Moreover, during 1995-2015, the intensity and extent of human activities increase by 15.35% and 40.64%, respectively. The superposition results of the HAI and frozen ground thawing hazard maps show that seasonally frozen ground region has relatively larger HAI, and its mean value is more than twice that of the permafrost region. For permafrost regions, the medium-hazard area has the highest HAI (0.09), which possibly has great impacts on the linear infrastructure. The establishment of a thawing disaster warning map can effectively shield high thaw settlement hazard areas without human activities and thus can present a more accurate early warning. These results can provide important scientific references for the disaster prevention and mitigation work in frozen ground regions, including risk assessment and infrastructure maintenance.